Pengaruh Jumlah Penduduk, Inflasi dan Produk Domestik Regional Bruto Terhadap Pajak Daerah Kota Medan Tahun 2019-2023 - Sabita Maghfirah; Emi Masyitah (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This research aims to analyze the influence of population, inflation, and Regional Gross Domestic Product (GDP) on local tax revenue in Medan City in the period of 2019 to 2023. Local tax is one of the main sources of income of the local government which is greatly influenced by macroeconomic and demographic conditions. This research uses a quantitative approach with secondary data obtained from the Central Statistics Agency (BPS) and other related agencies. The analysis technique used is multiple linear regression, with the help of SPSS software version 25. The analysis results show that simultaneously, population variables, inflation, and PDRB have a significant effect on local tax revenue. Partially, the population and PDRB show a positive and significant effect, which means that the greater the population and PDRB, the more local tax revenue tends to increase. Meanwhile, inflation shows a negative effect on local tax revenue, although it is not always statistically significant. This indicates that high price fluctuations can reduce people's purchasing power and hinder economic activity, which ultimately has an impact on a decrease in tax revenue. By understanding the influence of these three variables, local governments are expected to be able to design fiscal policies that are more responsive to economic and demographic dynamics, in order to optimize the potential for regional tax revenue in a sustainable manner. This research also provides empirical contributions in the study of regional economics, especially in the context of regional financial management.